2012
DOI: 10.4236/ojped.2012.21007
|View full text |Cite
|
Sign up to set email alerts
|

Central body fat distribution indices in Thai preschool children

Abstract: Background: Central obesity is associated with adverse health outcomes. This study aimed to determine the characteristics of central body fat distribution in Thai preschool children and to examine factors that could influence on body fat distribution of children. Methods: The total 811, 5 - 6 years old children were randomly sampled from 9 primary schools in Saraburi province. Body weight and height were measured in each child. Waist circumference (WC) was measured at the umbilicus level and hip circum-ference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
0
1
Order By: Relevance
“…The mean BMI in the study population was 19.10 (SD 5.44). The present BMI was higher than the previous study in Thai children in 2008 27 that revealed the mean BMI of 15.7 in girls and 16.2 in boys. This finding supports to the early detection of obesity and MetS in pediatric psoriasis population.…”
Section: Discussioncontrasting
confidence: 91%
“…The mean BMI in the study population was 19.10 (SD 5.44). The present BMI was higher than the previous study in Thai children in 2008 27 that revealed the mean BMI of 15.7 in girls and 16.2 in boys. This finding supports to the early detection of obesity and MetS in pediatric psoriasis population.…”
Section: Discussioncontrasting
confidence: 91%
“…In addition, compared with studies focused on relationship between body composition and common anthropometric indices (e.g. BMI, WC, and WHtR), studies investigated skinfolds and novel anthropometric parameters comprehensively in Asia are scarce (Kagawa et al 2008b, Kagawa et al 2010, Yamborisut et al, 2012, Liu et al 2020. The present study therefore aimed to examine the usefulness of anthropometric parameters in young Japanese females by assessing their association with indicators of adiposity obtained from a dual energy x-ray absorptiometry (DXA).…”
Section: Introductionmentioning
confidence: 98%